Environmental Recovery of Nosocomial Bacteria in a Companion Animal Shelter Before and After Infection Control Procedures - Horsman, Sara; Rynhoud, Hester; Zhou, Xiaoyan; Soares Magalhães, Ricardo J.; Gibson, Justine S.; Meler, Erika (Frontiers in Veterinary Science, 2021)
While the effects of cleaning and disinfection practices on the reduction of environmental nosocomial bacteria are well established in human and large animal veterinary hospitals, how animal movements within animal health care facilities influence environmental bacterial recovery is poorly understood. During three consecutive weeks, 155 electrostatic wipes were collected from the environment pre- and post-cleaning only or following disinfection from seven target locations within an animal shelter. All samples were cultured, and isolates were identified using a matrix-assisted laser desorption ionization – time of flight mass spectrometry. Social network analysis of animal movements during the sampling period was performed to estimate the level of connectivity of the seven sampling locations. The relationship between bacterial levels and connectivity estimates of the sampling locations were investigated using a negative binomial regression model with a random effect of sample location. Overall, our results indicate a significant reduction in the total bacterial contamination with disinfection when compared to cleaning only (Coefficient (Coef.) = -1.72, 95% Confidence Interval (CI) = -3.09, -0.34, P = 0.015). Higher total bacterial contamination was significantly more likely in sampled areas with less animal movement connectivity (Coef. = -0.32, 95% CI = -0.49, -0.15, P ≤ 0.001). Pseudomonas aeruginosa and ampicillin resistant Enterobacteriaceae (Escherichia coli, Enterobacter spp. and Klebsiella spp.) were present in the animal holdings and in the shelters’ veterinary clinic environment at all sampling times. Our findings demonstrate that cleaning followed by disinfection practices are effective at reducing environmental bacterial levels. Areas with less animal connectivity are more likely to have a higher bacterial contamination. These areas could represent environmental reservoirs for bacterial infection and should be targeted with effective cleaning and disinfection protocols.